Enhanced Cr(VI) stabilization in soil by carboxymethyl cellulose-stabilized nanosized Fe0 (CMC-nFe0) and mixed anaerobic microorganisms. (1st March 2020) - Su, Mei; Yin, Weizhao; Liu, Li; Li, Ping; Fang, Zhanqiang; Fang, Yili; Chiang, Penchi; Wu, Jinhua
Abstract: A collaborative system of carboxymethyl cellulose stabilized nanosized zero-valent iron (CMC-nFe 0 ) and microorganisms was set up to enhance the stabilization of Cr(VI) in soil. In comparison with an aqueous-bound Cr(VI) removal of 18.9% in the nFe 0 system, a higher Cr(VI) removal of 68.9% was achieved in the nFe 0 and microorganisms system after 14 d remediation because the microorganisms on the nFe 0 surface promoted nFe 0 corrosion and enhanced abiotic and biotic Cr(VI) stabilization by generating highly active minerals such as magnetite, lepidocrocite and green rust on the nFe 0 surface. As a stabilizing agent for nFe 0 and an organic substrate for microorganisms, CMC on the nFe 0 surface not only enhanced the dispersion of nFe 0, but also boosted the activity of microorganisms, resulting in a promotion of 0.9 and 0.5 times higher aqueous-bound Cr(VI) removal via the improvement of nFe 0 and microorganisms respectively, thus a total 4 times higher aqueous-bound Cr(VI) removal of 95.3% was achieved in the CMC-nFe 0 and microorganisms system as compared to the nFe 0 system. After 14 d remediation, easily available species of Cr(VI) and Crtotal, such as water soluble (WS), exchangeable (EX) and bounded to carbonates (CB), were mainly transformed to less available Fe–Mn oxides-bounded (OX) and residual (RS) species because of the production of ferrochrome precipitates (Crx Fe1-x OOH or Crx Fe1-x (OH)3 ). Besides, the stabilization of Cr(VI) in the CMC-nFe 0 and microorganisms system was pH-dependent and it increased with CMC-nFe 0 dosage. Due to excellent Cr(VI) stabilization and Cr immobilization, coupled CMC-nFe 0 and anaerobic microorganisms process is of great potential in remediating Cr(VI)-containing soil. Graphical abstract: Image 1 Highlights: A collaborative system of CMC-nFe 0 and mixed anaerobic microorganisms was set up. Microorganisms promoted iron corrosion, hydrogen release and active secondary minerals production. Cr species were mainly converted to less available Fe-Mn oxides-bounded and residual species.